Potential roles of serum ATPase and AMPase in predicting diagnosis of colorectal cancer patients. Issue 6 (1st June 2022) - Shi, Mengchen; Tian, Yu; He, Lingyuan; Zhang, Jingdan; Yang, Xiangling; Liu, Huanliang
ABSTRACT: Colorectal cancer (CRC) is a common gastrointestinal cancer with high incidence and mortality rates. CRC may be associated with regulation of circulating nucleotides. This study aimed to evaluate the serum levels of nucleotide-metabolizing enzymes (ATPase and AMPase) in patients with CRC and to explore the clinical diagnostic value of these enzymes. The gene set variation analysis (GSVA) score of the ATP-adenosine signature was calculated using tumor samples from The Cancer Genome Atlas (TCGA). ATP-adenosine signaling plays a central role in CRC progression. A total of 135 subjects, including 87 patients with CRC and 48 healthy controls, were included. The serum levels of ATPase and AMPase in the CRC group were significantly higher than those in the control group ( P < 0.05). Furthermore, ATP and AMP hydrolysis levels significantly increased in the advanced CRC group ( P < 0.05). ATP and AMP hydrolysis was decreased by the ENTPDase inhibitors (POM-1 and ARL67156) and CD73 inhibitor (APCP). The sensitivities of ATPase and AMPase were 95.4% and 75.9%, respectively, which were higher than those of CEA (67.8%) and CA19-9 (72.4%). The specificities of ATPase and AMPase were 69.9% and 73.9%, respectively, which were higher than that of CA19-9 (47.8%). The combination of CEA, ATPase, and AMPase demonstrated high sensitivity (92.0%) and specificity (87.0%). Collectively, ATPase and AMPase activities are upregulated in CRC with considerable diagnostic significance. The combination of CEA, ATPase, and AMPase may provide a novel approach for CRC screening. Graphical abstract: uf0001